The Impact of Human Resource Information Systems on Human Resource Management Effectiveness: A Study in Selected Large Apparel Firms in the Western Province of Sri Lanka - Perera, G.D.N.; Thalgaspitiya, U.K.; Wijewardene, L. (IJRDO - Journal of Applied Management Science, 2017)
Human Resource Information Systems (HRIS) play a significant role in the contemporary business world where it assists in achieving Human Resource Management (HRM) effectiveness. As a result, this study aims to inspect the impact of HRIS on HRM effectiveness in selected large apparel firms in the Western Province in Sri Lanka. HRIS was measured in terms of five dimensions (top management, effective communication, training, information system and human resource department) and HRM effectiveness was measured in recruitment, performance management and human resource planning functions. 12 large apparel firms were selected as the sample for the study and a self-administered survey was conducted covering employees in the entire HR department using the five point Likert scale of 28 statements. The data was analyzed and evaluated using the statistical data analysis package, SPSS (version 23.0) with univariate and bivariate methods. The results of the survey revealed that 85% of the variance in the HRM effectiveness is explained by HRIS. Further, findings of this study indicated that the selected large apparel firms in the Western Province use the HRIS in human resource planning, recruitment and performance management areas. Since the study was based on only three HRM functions, the researchers recommend the need to apply more HRM functions in order to discover the impact of HRIS on human resource management effectiveness for further researchers.